The influence of the mixing time in the rheological behavior of cement pastes - Bertolucci, F. S. [UNESP]; Barbosa, M. P. [UNESP]; De Freitas Maciel, G. [UNESP]; Dos Santos, F. L.; Salles, F. M. (My University, 2008)
Rheology has the purpose to study the flux and deformation of materials when submitted to some tension or outer mechanical solicitation. In practice, the effective scientific field broached by rheology is restricted only to the study of homogeneous fluids behavior, in which are included eminent liquids, particles suspensions, and emulsions. The viscosity (η) and the yield stress (τ 0) are the two basic values that define the fluids' behavior. The first one is the proportionality constant that relates the shear rate (γ) with the shear stress (τ) applied, while the second indicates the minimal tension for the flowage beginning. The fluids that obey the Newton's relation - Newtonians fluids - display the constant viscosity and the null yield stress. It's the case of diluted suspensions and grate amount of the pure liquids (water, acetone, alcohol, etc.) in which the viscosity is an intrinsic characteristic that depends on temperature and, in a less significant way, pressure. The suspension, titled Cement Paste, is defined as being a mixture of water and cement with, or without, a superplasticizer additive. The cement paste has a non-Newtonian fluid behavior (pseudoplastic), showing a viscosity that varies in accord to the applied shear stress and significant deformations are obtained from a delimited yield stress. In some cases, systems can also manifest the influence of chemical additives used to modify the interactions fluid/particles, besides the introduced modifications by the presence of incorporated air. To the cement paste the rheometric rehearsals were made using the rheometer R/S Brookfield that controls shear stress and shear rate in accord to the rheological model of Herschel-Bulkley that seems to better adapt to this kind of suspension's behavior. This paper shows the results of rheometrical rehearsals on the cement paste that were produced with cements HOLCIM MC-20 RS and CPV-ARI RS with the addition of superplasticizer additives based of napthaline and polycarboxilate, with and without a constant agitation of the mixture. The obtainment of dosages of superplasticizer additives, as well as the water/cement ratio, at the cement at the fluidify rate determination, was done in a total of 12 different mixtures. It's observed that the rheological parameters seem to vary according to the cement type, the superplasticizer type, and the methodology applied at the fluidity rate determination.
Keywords: Cement; Mixing; Pastes; Cement paste; Cement type; Chemical additive; Herschel-Bulkley; Homogeneous fluids; Intrinsic characteristics; Mechanical solicitations; Mixing time; Newtonians; Non-Newtonian fluids; Particles suspension; Pseudoplastic; Pure liquids; Rheological behaviors; Rheological models; Rheological parameter; Scientific fields; Shear rates; Superplasticizer; Water/cement ratio; Acetone; Chemical modification; Concrete mixing; Elasticity; Liquids; Mixtures; Oil well cementing; Organic polymers; Plasticity; Rapid solidification; Rheology; Shear deformation; Shear stress; Strength of materials; Suspensions (fluids); Viscosity; Yield stress; Cement additives